Search for t ̄tH production in the H → bb ̄ decay channel with leptonic t ̄t decays in proton-proton collisions at √s = 13 TeV - (:unkn) unknown (My University, 2019)
Abstract A search is presented for the associated production of a standard model Higgs boson with a top quark-antiquark pair...